Effects of contact path on lubricant distribution and EHL film formation - Xuyang Jin; Xinming Li; Linqing Bai; He Chong; Feng Guo; Gerhard Poll; Yongqiang Fu (Friction)
The dynamic motion of the rolling elements in rolling bearings leads to variations in the contact paths. The displacement of the rolling tracks and the contact width between adjacent rolling elements redistribute the lubricant, consequently influencing film formation. To reproduce this process, an auxiliary ball is introduced into the conventional ball-on-disc test device. By adjusting the positions and loading conditions of the auxiliary balls, the influences of the offset distance (L) and contact width on lubricant redistribution and film formation can be experimentally observed. The results demonstrate that as L increases, both the inlet lubricant supply and the lubrication state improve. At high loads, the auxiliary ball generates a wider rolling track, resulting in a decrease in film thickness due to inadequate inlet lubricant supply. Furthermore, numerical simulations were conducted to validate these observations. The results confirm that dynamic ball motion significantly influences lubricant redistribution and plays a vital role in determining film thickness. The underlying mechanisms were analyzed and elucidated. The findings provide valuable insights into the lubrication behavior of rolling bearings induced by the dynamic motion of rolling elements.